Nutritional Benefits And Health Effects Of Fermented Pomegranate Juice With Lactobacillus Plantarum ATCC 11842 - kelloua halima dalila; Benbouziane bouassria; Dahou abdelkader el Amine; Adjoudj fatma (Revista Electronica de Veterinaria, 1970)
This study investigates the fermentation of pomegranate juice from four local cultivars—CV (Centre Ville d’Oran, acidic), MOS (Mosta Sefri, non-organic), EU (Tlelet Oran, irrigated with wastewater), and SP (Saint Remy, sweet)—using Lactobacillus plantarum ATCC 11842. Fermentation significantly influenced cell viability, phenolic activity, antioxidant capacity, and sensory qualities over a four-week storage period. Initial cell counts of 8 log cfu/mL remained stable for three weeks before declining to values between 5.99 log cfu/mL (SP) and 6.10 log cfu/mL (EU) by week four, maintaining levels above the probiotic threshold. MOS exhibited the highest total phenolic and flavonoid contents (0.99 mg GAE/100 mL and 0.215 mg QEE/L, respectively). Antioxidant activity peaked at d21 for FRAP (44.49 mmol Trolox/L) and varied for DPPH across samples. Fermentation preserved sensory attributes, with fermented juices maintaining superior aroma, taste, and overall quality scores compared to non-fermented samples, which deteriorated by week four. These findings emphasize the role of Lactobacillus plantarum in enhancing both the nutritional and sensory profiles of pomegranate juice through sustained phenolic activity, bioactive compound production, and antioxidant capacity. The study highlights the potential of probiotic fermentation as a strategy for developing health-promoting beverages with extended shelf life and improved functional properties.